Biogeography, diversity and environmental relationships of shelf and deep-sea benthic Amphipoda around Iceland - Anne-Nina Lörz; Stefanie Kaiser; Jens Oldeland; Caroline Stolter; Karlotta Kürzel; Saskia Brix (PeerJ, 2021)
The waters around Iceland, bounding the Northern North Atlantic and the Nordic seas, are a region characterized by complex hydrography and seabed topography. This and the presence of the Greenland-Iceland-Faroe-Scotland ridge (GIFR) are likely to have a major impact on the diversity and distribution of the benthic fauna there. Biodiversity in this region is also under increasing threat from climate-induced changes, ocean warming and acidification in particular, affecting the marine realm. The aim of the present study was to investigate the biodiversity and distributional patterns of amphipod crustaceans in Icelandic waters and how it relates to environmental variables and depth. A comprehensive data set from the literature and recent expeditions was compiled constituting distributional records for 355 amphipod species across a major depth gradient (18–3,700 m). Using a 1° hexagonal grid to map amphipod distributions and a set of environmental factors (depth, pH, phytobiomass, velocity, dissolved oxygen, dissolved iron, salinity and temperature) we could identify four distinct amphipod assemblages: A Deep-North, Deep-South, and a Coastal cluster as well as one restricted to the GIFR. In addition to depth, salinity and temperature were the main parameters that determined the distribution of amphipods. Diversity differed greatly between the depth clusters and was significantly higher in coastal and GIFR assemblages compared to the deep-sea clusters north and south of the GIFR. A variety of factors and processes are likely to be responsible for the perceived biodiversity patterns, which, however, appear to vary according to region and depth. Low diversity of amphipod communities in the Nordic basins can be interpreted as a reflection of the prevailing harsh environmental conditions in combination with a barrier effect of the GIFR. By contrast, low diversity of the deep North Atlantic assemblages might be linked to the variable nature of the oceanographic environment in the region over multiple spatio-temporal scales. Overall, our study highlights the importance of amphipods as a constituent part of Icelandic benthos. The strong responses of amphipod communities to certain water mass variables raise the question of whether and how their distribution will change due to climate alteration, which should be a focus of future studies.